Development and validation of gas chromatography-mass spectrometric method for the determination of epoxidized soybean oil in foods stored in glass jars with metal lids - Hong, Keat Quek; Mohd Marsin Sanagi,; Wan Aini Wan Ibrahim,; Syairah Salleh,; Mazidatulakmam Miskam, (Universiti Kebangsaan Malaysia, 2014)
A method has been developed for the determination of epoxidized soybean oil (ESBO) in oily foods stored in glass jars with metal lids using gas chromatography-mass spectrometry (GC-MS). ESBO and its internal standard (cis,cis-11,12;14,15-diepoxyeicosanoate) were isolated from the matrix by transesterification process. The developed method showed good linear dynamic range between 0.7-20 μg mL-1 with coefficients of determination (R2) > 0.9968 and acceptable limit of detection and limit of quantitation of 7 and 23 mg kg-1, respectively, based on linearity calculations. Analyte recoveries were 90.84±27.24% for low concentration, 78.05±11.59% for medium concentration and 99.23±10.20% for high concentration. This first fully validated GC-MS method was successfully applied for the determination of ESBO in foods stored in glass jar with metal lid. Among the 31 food samples studied, 6 samples were found to exceed the specific migration limit of 60 mg kg-1 (based on EU Directive 2002/72/EC). The developed method is thus potentially useful for routine analysis for the determination of ESBO.